2007
DOI: 10.1021/es062178c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Disinfection Byproduct Precursors Based on Hydrophobicity and Molecular Size

Abstract: Natural organic matter (NOM) from five water sources was fractionated using XAD resins and ultrafiltration membranes into different groups based on hydrophobicity and molecular weight (MW), respectively. The disinfection byproduct formation from each fraction during chlorination and chloramination was studied. In tests using chlorination, hydrophobic and high MW (e.g., >0.5 kDa) precursors produced more unknown total organic halogen (UTOX) than corresponding hydrophilic and low MW (e.g., <0.5 kDa) precursors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
206
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(243 citation statements)
references
References 22 publications
(57 reference statements)
22
206
3
5
Order By: Relevance
“…In other research, it was found that a significant portion of the TOX produced during chlorination or chloramination was of a high molecular weight (Khiari et al 1997;Hua & Reckhow 2007). An analytical constraint in further identification of TOX components has been that GC/MS, a principal measurement tool, can only typically be used to identify DBPs with molecular weights of up to approximately 650 Da.…”
Section: Other Emerging Disinfection By-products Of Concernmentioning
confidence: 98%
“…In other research, it was found that a significant portion of the TOX produced during chlorination or chloramination was of a high molecular weight (Khiari et al 1997;Hua & Reckhow 2007). An analytical constraint in further identification of TOX components has been that GC/MS, a principal measurement tool, can only typically be used to identify DBPs with molecular weights of up to approximately 650 Da.…”
Section: Other Emerging Disinfection By-products Of Concernmentioning
confidence: 98%
“…However, the role of aluminum speciation in THM and HAA precursor removal was different. Some investigations indicated that THM and HAA had different precursors (23,24). In their results, aliphatic structures played a more important role in THM formation than HAA formation, while HAAs had more aromatic structures as their precursors than THMs.…”
Section: Role Of Aluminum Speciation In Removal Of Dbp Precursors Witmentioning
confidence: 99%
“…This method separates NOM into several components according to their chemical properties (hydrophilicityhydrophobicity). Based on this method, the behaviors of different NOM fractions have been investigated (Chow et al, 2005;Hua and Reckhow, 2007;Kitis et al, 2002;Krasner et al, 1996;Liang and Singer, 2003;Matilainen et al, 2011;Panyapinyopol et al, 2005). The results showed that the hydrophilic fractions of NOM are composed mostly of aliphatic carbon and nitrogen compounds (such as carbohydrates, sugars, and amino acids), while hydrophobic NOM primarily consists of humic and fulvic acids and is rich in aromatic carbon, phenolic structures and conjugated double bonds (Krasner et al, 1996).…”
Section: Introductionmentioning
confidence: 99%